2019
DOI: 10.1088/1361-6455/ab26e0
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap on photonic, electronic and atomic collision physics: II. Electron and antimatter interactions

Abstract: We publish three Roadmaps on photonic, electronic and atomic collision physics in order to celebrate the 60th anniversary of the ICPEAC conference. In Roadmap II we focus on electron and antimatter interactions. Modern theoretical and experimental approaches provide detailed insight into the many body quantum dynamics of leptonic collisions with targets of varying complexity ranging from neutral and charged atoms to large biomolecules and clusters. These developments have been driven by technological progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 189 publications
0
20
0
Order By: Relevance
“…The values of mass stopping power of α-particles in air at different pressure have been presented in Table 1. They have been calculated by Equation (2). The results show that the mass stopping power increases as the air pressure increases.…”
Section: Figure 2 Energy Loss Of Alpha Particles In Air As a Function Of Distance For Different Values Of Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…The values of mass stopping power of α-particles in air at different pressure have been presented in Table 1. They have been calculated by Equation (2). The results show that the mass stopping power increases as the air pressure increases.…”
Section: Figure 2 Energy Loss Of Alpha Particles In Air As a Function Of Distance For Different Values Of Pressurementioning
confidence: 99%
“…Nuclear radiation is said to be ionizing when it possesses a high enough kinetic energy to be able to eject electrons from the atom of any medium it traverses or collides with. This loss of electrons causes the target atom to become positively charged [1,2]. There are two major types of ionizing radiations: directly and indirectly ionizing radiations.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate experimental data concerning electron interactions are also important for the description of many phenomena occurring in plasma physics and gaseous electronics [25,26], including modeling of processes in cometary and planetary atmospheres [27][28][29]; they are also of great importance for modern technologies including focused electron beam induced deposition (FEBID) [30,31]. More details on the present status of electron collision physics including preview of electron collisions theory, electronmolecule interactions, ionization and dissociative electron attachment studies with the summary of the future challenges can be found in one of the road maps on photonic, electronic and atomic collision physics [32].…”
Section: Introductionmentioning
confidence: 99%
“…The physics of electron scattering from molecules has been a focus of research in atomic and molecular physics for decades. These scattering processes possess both fundamental and applied interest [1]. Electron scattering experiments allow an insight into, for example, the electronic structure of molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%